Lucio Phenomenon and APLA in Hansen’s Disease: A Rare Phenomenon - Jayanta Sharma; Sudipto Chakroborty; Kisholoy Karan; Parthajit Das (Bengal Physician Journal)
Lucio phenomenon (LP) is a rare reactional state seen in cases of diffuse lepromatous leprosy. Lucio leprosy is a pure, primitive, and diffuse form of lepromatous leprosy. It is observed almost exclusively in Mexico and Central America and is considered a globally restricted phenomenon. However, isolated cases are being reported worldwide. Patients with Lucio leprosy often present with manifestations of LP, which includes purpuric macules with multiple and extensive areas of ulceration with bizarre-patterned, angulated borders mainly affecting the extremities. Lucio phenomenon is difficult to recognize, especially in nonendemic countries, which can lead to a delay in its diagnosis and management. We report a case of LP due to its occurrence in the classical form of lepromatous leprosy and rarity in Eastern India.